2012
DOI: 10.3892/ijmm.2012.916
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of peroxiredoxin 3 as a biomarker in hepatocellular carcinoma by a proteomic approach

Abstract: Abstract. Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide with poor prognosis due to resistance to conventional chemotherapy and limited efficacy of radiotherapy. Thus, alternative therapeutic strategies need to be established. In order to search for a useful biomarker to improve its efficacy, we conducted a two-dimensional gel electrophoresis and MALDI-TOF MS-based comparative proteomic analysis to profile the differentially expressed proteins between HCC tumor tissues with his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…PRX3 is consistently up-regulated in prostate cancers [55], is over-expressed in greater than 90% of hepatocellular carcinomas [56], and increases in abundance during malignant progression of cervical cancer [57]. Inhibition of PRX3 expression in breast cancer cells induces cell cycle arrest and impairs cell proliferation [58].…”
Section: Discussionmentioning
confidence: 99%
“…PRX3 is consistently up-regulated in prostate cancers [55], is over-expressed in greater than 90% of hepatocellular carcinomas [56], and increases in abundance during malignant progression of cervical cancer [57]. Inhibition of PRX3 expression in breast cancer cells induces cell cycle arrest and impairs cell proliferation [58].…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing more sensitive machines and methods, low abundance proteins that change with cancer development can be found and may be more directly related to the cancer. Using such methods, proteins such as peroxiredoxin 3 (Ai et al, 2006; Chen et al, 2010b; Guo et al, 2007; Li et al, 2008; Lu et al, 2010; Qiao et al, 2012; Song et al, 2009; Wang, 2007; Yue et al, 2007) and osteopontin have been identified as potential markers of HCC (Abu El Makarem et al, 2011; Chen et al, 2010a; Chen et al, 2011; Kim et al, 2006; Lin et al, 2011; Phillips et al, 2012; Qin and Tang, 2004; Shang et al, 2012; Tang et al, 2004; Ye et al, 2003; Zekri et al, 2011). While these markers have been shown to be elevated in other cancers, they may still have great value in the early detection of liver cancer (Chahed et al, 2008; Lehtonen et al, 2004; McAllister et al, 2008; Mirza et al, 2008; Park et al, 2008; Park et al, 2007; Reiniger et al, 2007; Schremmer et al, 2007; Tigrani and Weydert, 2007; Tuck et al, 2007; Whiteaker et al, 2007).…”
Section: Proteomic Identification Of Biomarkers Of Liver Cancermentioning
confidence: 99%
“…Numerous genomic and proteomic screening studies have been employed to identify potential biomarkers of HCC[18-24] but to date the markers identified in these studies have not been clinically fruitful. Because the liver is the hub of carbohydrate, amino acid, and lipid metabolism[25,26], chronic liver diseases undoubtedly disrupt normal metabolic function.…”
Section: Introductionmentioning
confidence: 99%